Family: a study of the role of ritual and it's effects on the Kansas State football team - Hanson, Zachary R. (Kansas State University, 2014)
“Family” is a sacred concept to the Kansas State football team. Calling a group of 100 plus players from across the nation and ten coaches a family is a unique concept when it is viewed from the outside. However, if you have been a part of the rituals involved in it, you understand. This research project examines the role of ritual in the “family” environment of Kansas State football and how that affects young men from different sociological backgrounds by interviewing 20 current and past players in the program. Though the findings showed that this culture affected all respondents in a positive way, it was also discovered that 4 particular young men who grew up with less family support were affected more than those who felt supported by their family from a young age.
Keywords: Family; Ritual; Football; Sociology (0626)